Evolution of ASC Immunophenotypical Subsets During Expansion In Vitro - Peng, Qiuyue (Int J Mol Sci, 2020)
Adipose-derived stromal/stem cells (ASCs) are currently being considered for clinical use for a number of indications. In order to develop standardized clinical protocols, it is paramount to have a full characterization of the stem cell preparations. The surface marker expression of ASCs has previously been characterized in multiple studies. However, most of these studies have provided a cross-sectional description of ASCs in either earlier or later passages. In this study, we evaluate the dynamic changes of 15 different surface molecules during culture. Using multichromatic flow cytometry, ASCs from three different donors each in passages 1, 2, 4, 6, and 8 were analyzed for their co-expression of markers associated with mesenchymal stem cells, wound healing, immune regulation, ASC markers, and differentiation capacity, respectively. We confirmed that at an early stage, ASC displayed a high heterogeneity with a plethora of subpopulations, which by culturing became more homogeneous. After a few passages, virtually all ASCs expressed CD29, CD166 and CD201, in addition to canonical markers CD73, CD90, and CD105. However, even at passage 8, there were several predominant lineages that differed with respect to the expression of CD34, CD200 and CD271. Although the significance of remaining subpopulations still needs to be elucidated, our results underscore the necessity to fully characterize ASCs prior to clinical use.